Friendship in the age of loneliness : an optimist's guide to connection - Poswolsky, Smiley (Running Press, 2021)
"After a year of social distancing and lockdown measures during the pandemic, it's more clear than ever that our friendships and social bonds are vital to our health and happiness. This refreshing, positive guide helps you take care of your people and form deep connections in the digital age. We are lonelier than ever. The average American hasn't made a new friend in the last five years. Research has shown that people with close friends are happier, healthier, and live longer than people who lack strong social bonds. But why--when we are seemingly more connected than ever before--can it feel so difficult to keep those bonds alive and well? Why do we spend only four percent of our time with friends?"--Amazon.